MORPHOLOGICAL FEATURES OF THE GALLBLADDER WALL WITH MIXED ANIMAL NUTRITION - Ryabushko, E.B. (World of Medicine and Biology, 2015)
For the bottom wall of the mucosa of the gallbladder pig (Sus domestica) is characterized by some differences of relief. In the central part there are protrusions, various width and height. Among them are narrow and relatively high protrusion, but bulk up wide and low, who in sections reminiscent of the bell, the base of which is addressed to the lamina propria mucosa. Note the tops of the bell-shaped protrusion. In most low protrusion is rounded, but also increase the height of the tip protrusion gradually extended and rounded forms a narrow peak.Own the bottom plate of the mucosa of the gallbladder pigs rather broad and relatively dense, it consists of a winding fibers of connective tissue. In the lamina propria are numerous small lymph nodules. The shape of these nodules often incorrectly oval, sometimes there are spherical nodules. Characteristically, lymphoid tissue, referred to as nodes, located directly under the mucous membrane. As the thickness of the lamina propria scattered isolated blood vessels like arterioles and venules so. In some places you can observe small lymph vessels that are characteristic of the thin wall and uneven gaps. Peripheral submuskulyarnoyi membrane layer in contact directly with muscular shell, represented grubovoloknistye connective tissue, which is built of thick collagen fibers winding or groups. Thus, if the inner layer submuskulyarnoyi shell by winding thin connective tissue fibers, in general, looks dribnokomirkovoyi sections of the grid, the outer layer between the fibers or bundles formed slit-like spaces.The muscular coat the bottom of the gallbladder thin plate represented compactly arranged smooth muscle fibers with circular direction. It should be noted that this shell is sometimes winding. In some areas it thickens, and in others narrowing. Sometimes there is a slight easing of the shell.The outer shell of this part of the gallbladder winding consists of thin connective tissue fibers with circular direction. These fibrous structures form a thin plate, located between the muscle and serous membranes. Draws attention to a significant reduction in the number of blood and lymph vessels in the membrane, compared with lamina propria mucosa.Muscular body shell gall bladder characterized by circular direction and looks rather wide plate. In some areas of the plate there tortuosity fibers. Generally, this plate is not the same. The outer layer consists of densely arranged muscle fibers. On the surface, this compact layer sometimes appear eosinophilic transverse constriction, which obviously hinder easing muscle bundles. It is likely that such constriction formed as local thickening peremiziyu. Such banners are usually placed evenly along the muscle bundle. In some parts of the muscle layer of splitting observed in muscle bundles or individual smooth muscle fibers. In these structural elements of the muscle layer perymizialni banners disappear.Perymuskulyarna connective tissue sheath contains cells, pronounced, loosening. Its thickness in the wall of the gallbladder body changes. Along with bulges where there are often relatively large blood vessels (arterioles and venules) are more subtle areas in which the said vascular structures are usually absent. Most of the vascular membrane elements are compact, in the form of bundles containing small arterioles, venules and small lymphatic vessels.Perymuskulyarna or subserous shell is constructed of dense connective tissue and is broad and compact. In some places in this shell scattered small blood and lymphatic vessels. A feature of this membrane should consider the presence of small glandular elements.
Keywords: gallbladder; cystic duct; cholecystitis; cholelithiasis